Nitric Oxide in Selective Cerebral Perfusion Could Enhance Neuroprotection During Aortic Arch Surgery - Linardi, Daniele; Mani, Romel; Murari, Angela; Dolci, Sissi; Mannino, Loris; Decimo, Ilaria; Tessari, Maddalena; Martinazzi, Sara; Gottin, Leonardo; Luciani, Giovanni B.; Faggian, Giuseppe; Rungatscher, Alessio (Frontiers in Cardiovascular Medicine, 2022)
Background: Hypothermic circulatory arrest (HCA) in aortic arch surgery has a significant risk of neurological injury despite the newest protective techniques and strategies. Nitric oxide (NO) could exert a protective role, reduce infarct area and increase cerebral perfusion. The present study aims to investigate the possible neuroprotective effects of NO administered in the oxygenator of selective antegrade cerebral perfusion (SCP) during HCA. Methods: Thirty male SD adult rats (450-550g) underwent cardio-pulmonary bypass (CPB), cooling to 22°C body core temperature followed by 30 minutes of HCA. Rats were randomized to receive SCP or SCP added with NO (20 ppm) administered through the oxygenator (SCP-NO). All animals underwent CPB assisted rewarming to a target temperature of 35°C in 60 minutes. At the end of the experiment, rats were sacrificed, and brain collected. Immunofluorescence analysis was performed in blind conditions. Results: Neuroinflammation assessed by Iba1 expression, a microglia activation marker was lower in SCP-NO compared to SCP (4.11 ± 0.59% vs 6.02 ± 0.18%; p < 0.05). Oxidative stress measured by 8oxodG, was reduced in SCP-NO (0.37 ± 0.01% vs 1.03 ± 0.16%; p<0.05). Brain hypoxic area extent, analyzed by thiols oxidation was attenuated in SCP-NO (1.85 ± 0.10 % vs 2.74 ± 0.19 %; p<0.05). Furthermore, the apoptotic marker Caspases 3 was significantly reduced in SCP-NO (10.64 ± 0.37% vs 12.61 ± 0.88%; p<0.05). Conclusions: NO administration in the oxygenator during SCP and HCA improves neuroprotection by decreasing neuroinflammation, optimizing oxygen delivery by reducing oxidative stress and hypoxic areas, finally decreasing apoptosis.